Assessment of waste workers occupational risk to microbial agents and cytotoxic effects of mixed contaminants present in the air of waste truck cabin and ventilation filters - Marchand, Genevieve (2024)
2018–0016 and the H&TRC authors gratefully acknowledge the national support of Fundação para a Ciência e a Tecnologia / Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES) through the UIDB/05608/2020 and UIDP/05608/2020. The authors would like to thank Tam Nguyen, Patrick Genest, Edith Giasson, Julien Trépanier, Noémie Gervais, and Fabiola Salambanga, who helped on sampling day and in some lab analysis. They would also like to thank all the workers and the waste management companies that participated in this project. Publisher Copyright: © 2024 The Author(s). Published with license by Taylor & Francis Group, LLC.